Photoredox-Catalyzed Ring-Opening Addition Reaction between Benzyl Bromides and Cyclic Ethers - Kuang, Cuiwen; Ni, Chuanfa; Gu, Yucheng; Hu, Jinbo (Synthesis, 2021)
A novel nucleophilic reaction between cyclic ethers and benzyl bromides is achieved under photoredox catalysis. The reaction proceeds through a single-electron-transfer (SET) pathway rather than a common SN2 mechanism. By two steps of reduction and oxidation, a benzyl bromide heterolyzes to give a carbocation and bromide ion under mild conditions, and then a cyclic ether captures both the carbocation and bromide ion to afford the addition product.
Keywords: photoredox catalysis; carbocation; cyclic ether; benzyl bromide; ring-cleavage addition reaction; fluorine